Karakterisasi dan Aplikasi Arang Aktif Batang Pisang untuk Adsorpsi Remazol Brilliant Blue dalam Limbah Industri Batik - Junita Darmawarni; Farid Ramadhan; Susanto, Susanto; Siti Warnasih (Yayasan Literasi Sains Indonesia, 2025)
The batik industry produces waste containing dyes from the process of dyeing batik cloth. Remazol brilliant blue (RBB) is a reactive dyestuff, used in the fabric dyeing process. RBB levels in waste can be reduced by means of adsorption using activated banana stem charcoal. This study aims to make, characterize and test the quality of activated charcoal from banana stems, determine the optimum conditions, adsorption capacity and RBB adsorption isotherm model and its application in absorbing RBB in Bogor batik industrial waste. The results showed that the intensity of the functional groups in the FTIR spectrum of activated charcoal was greater, with the surface morphology in SEM indicating that the pores of the activated charcoal were more open than the charcoal before activation. The quality of activated banana stem charcoal meets the requirements of SNI No.06-3730-1995 for 0.63% moisture content, 13.30% volatile matter content, 80.67% carbon content and 88.65 mg/g methylene blue absorption capacity. Optimum adsorption conditions occurred at pH 8, contact time 120 minutes, and 1 gram weight of activated charcoal for 50 mL of batik waste. The adsorption process suitable for the adsorption of remazol brilliant blue is the Freundlich isotherm with a maximum adsorption capacity of 10.7411 mg/g and an adsorption efficiency of 96.29%. Characterization of batik waste after adsorption meets the requirements of PermenLHK No.16 of 2019 for parameters pH 8.37, color test 194.3 PtCo and Total Suspended Solid (TSS) 38.6 mg/L.